2008
DOI: 10.1093/esr/jcn027
|View full text |Cite
|
Sign up to set email alerts
|

Bridge or Trap? Temporary Workers' Transitions to Unemployment and to the Standard Employment Contract

Abstract: Citation: Gash, V. (2008). Bridge or trap? To what extent do temporary workers make more transitions to unemployment than to the standard employment contract. European Sociological Review, 24(5), pp. 651-668. doi: 10.1093/esr/jcn027 This is the accepted version of the paper.This version of the publication may differ from the final published version. 1984;Blossfeld and Rohwer 1995). This paper establishes higher rates of transition to permanent employment than to unemployment for most temporary workers, tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
148
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(163 citation statements)
references
References 23 publications
6
148
1
8
Order By: Relevance
“…Gash (2008) nd empirical evidence for xedterm contracts to be a bridge to an open-ended contract. Moreover, McGinnity et al (2005) show that xed-term contracts are often used as a tool to screen new employees during the transition from education to work for West Germany.…”
Section: Temporary Employment and Screeningmentioning
confidence: 94%
“…Gash (2008) nd empirical evidence for xedterm contracts to be a bridge to an open-ended contract. Moreover, McGinnity et al (2005) show that xed-term contracts are often used as a tool to screen new employees during the transition from education to work for West Germany.…”
Section: Temporary Employment and Screeningmentioning
confidence: 94%
“…I denne studien benyttes AKU for perioden 2000 til 2009 til å identifisere personer som har vaert arbeidsledige, fast eller midlertidig ansatt. I tidligere studier av hvorvidt midlertidige stillinger fungerer som en bro, har faste stillinger gjerne vaert brukt som en indikator på om vedkommende har kommet over i en normal, typisk, og stabil tilknytningsform til arbeidslivet (Bosch 2004;Gash 2008;Vosko 2010). Vi ønsker imidlertid å studere slike overganger over et lengre tidsspenn.…”
Section: Innledningunclassified
“…An analysis of the European Community Household Panel study showed the differences in transition rates from fixed-term to permanent contracts in France, West Germany, Denmark and the UK between 1995 and 2001 [10]. Significant differences in the transition probabilities were apparent, with the highest rates in Germany and the UK, followed by Denmark and France.…”
Section: Cross-country Studiesmentioning
confidence: 99%